THE EFFECTIVENESS OF USING GRAMMATICAL CONSCIOUSNESS-RAISING TASK (GCRT) TOWARD STUDENTS’ GRAMMAR COMPREHENSION AT THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT IAIN BUKITTINGGI - Veni Roza (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Grammar as a micro skill is often deemed as a difficult and boring subject in learning a language inasmuch as it is a study of number of patterns or rules. This judgment unconsciously causes the difficulty for learners to learn in spite of it has been learned in several levels. To cope with this problem, Grammar Consciousness Raising Task (GCRT) strategy was used to help English Education Department students in order to master grammar. The procedure in GCRT includes discovery, consolidation, and use.  In this research paper, the researcher explained that the GCRT strategy was effective to be used in grammar class, seen from the students’ test results which was 78,9% and it is categorized into effective based on the effectiveness scale.